SISTEM INFORMASI PEMBUKUAN BERBASIS WEB PADALA BRUNDORE COOKIES SEMARANG (Information Technology and Telematics, 2013)
Abstract - Application of the accounting system is a technology to facilitate the  accounting activities of each business. La Brundore Cookies Semarang is a home-based   business  that  specializes  in  making pastries. This home-based  business   is  always concerned with the health aspects but still no less delicious than usual pastries. One of the  problems that La Brundore Cookies facing is the bookkeeping in every transaction but still manual. This  system  uses  development  life  cycle  system methodology that has five stages: planning, analysis, design, implementation and evaluation. This system wasbuilt  with  PHP   programming  language  and MySQL database.The    Advantage of  this programming language is create a dynamic website, easy to make and free of charge (freeware). Keywords : Home Industry, System  Development Life Cycle, Website, Accounting.